The EU claims that the Doha Development Round is good for development - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
Speaking in Brazil on January 30th 2003, the EU Trade Commissioner Pascal Lamy...